Peacebuilding: Reaching the rest of the world - Pethick, Ted; Zuehlke, Gus A. (Technical Centre for Agricultural and Rural Cooperation, 2008)
The war in northern Uganda has driven thousands of people from their homes to live in camps. Now, after a lot of trial an error, BOSCO Uganda has brought the internet and low-cost phone calls to the camps, giving the people a chance to tell their own story.